Upper extremity injury evaluation an interactive approach - Wiksten, Denise; Barry, Brian (Thorofare, NJ : SLACK Inc., 2000)
In this CD-ROM, three dimensional anatomical models allow one to take a virtual reality tour of pertinent anatomy and view models from all angles
Title from disc label
System requirements: Pentium 100 or faster processor; Windows 95, 98 or NT 4.0 or later; 2X CDROM drive; 16 MB of RAM; 1 MB SVGA video card; 8-bit Sound Blaster-compatible sound card; Quick Time 3.0 or higher for Windows
System requirements: Power PC processor; Mac OS version 7.5 or later; 2X CDROM drive; 16 MB of RAM; Quick Time 3.0 or higher for Macintosh
Keywords: Arm Injuries -- diagnosis; Arm -- anatomy & histology